(untitled) (Al Basirah, 2024)
Meat consumption has become the basic need of a human societies. According to Islamic Shariah, Allah the Creator, has allowed humans to consume the meat of halal animals and has stated a complete procedure of slaughtering the legally permitted animals. Adopting this process ensures the meat lawful for human consumption. There are other methods and practices of slaughtering and killing animals followed by different people of different religions and thoughts. In the modern world various techniques are being used to kill animals on mass level in slaughterhouses. Gas chambers, electric current, rods and mechanical knives are used for this purpose. The users of these practices claim that these techniques make the slaughtering process easier and more convenient for the animal as compare to the shariah guided ways of slaughtering. In this article I have discussed various procedures of slaughtering and killing an animal. I have analyzed these procedures in order to find out the most convenient way for the animal. I have also discussed the impact of slaughtering process on the end product; the meat and its effect on human health. This article concluded that shariah guided way of slaughtering is the most convenient way of slaughtering and the animal bears less pain as compared to the rest of the methods and the meat produced as a result of shariah way of slaughtering is healthier and has better psychological impact on human’s health.